Designing a Knowledge-Based Performance Management System and Web-Based Inventory Recording System for Medical Device Distributors: Case Study of PT. Mulawarman Mitra Medika - Fabian Zaki Geraldy Hasibuan; Dermawan Wibisono (Program Pascasarjana STIE Amkop Makassar, 2026)
PT. Mulawarman Mitra Medika, a medical device distributor in Indonesia, faces operational challenges including declining revenue growth, poor inventory accuracy, extended stock opname cycles, and limited strategic performance visibility. This study proposes an integrated approach combining a Knowledge-Based Performance Management System (KBPMS) with a web-based inventory recording system to address these challenges. Using mixed methods—qualitative process mapping, stakeholder interviews, and quantitative analysis via Analytical Hierarchy Process (AHP)—the research identifies 22 performance variables across three perspectives: Business Result, Internal Process, and Resource Capability. AHP prioritization reveals revenue growth, stock opname cycle time, and system user adoption rate as critical levers for improvement. The paper presents a complete design and implementation roadmap, including system architecture, data flow diagrams, entity relationship models, service level agreements, and a three-month phased rollout plan. The proposed KBPMS-integrated web system is expected to reduce data entry errors, shorten inventory cycles, improve reporting reliability, and strengthen strategic alignment. This research contributes both practical guidance for SMEs in healthcare distribution and theoretical insights into integrating digital systems with performance management frameworks in developing-economy contexts.